Women and education in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
The five Year Malaysia Plans That serve as the blueprint for Development in our country emphasize. The importance of education for Sustained economic growth. It is also recognized that gender equality in Access to education is necessary if More women are to contribute towards Social and economic development. This article describes the education Status of Malaysian women and How this relates to their employment Prospects.